2022
DOI: 10.1038/s41598-022-07454-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hip abductor and adductor strength on dynamic balance and ankle biomechanics in young elite female basketball players

Abstract: This study aimed to evaluate, in an isolated and relative manner, hip abductor (ABD) and adductor (AD) strength and to study the extent to which these factors are related to balance and ankle dorsiflexion mobility in young elite female basketball players. Sixty trainee-level elite female basketball players (13–18 years old), who voluntarily agreed to participate in the study, were divided into three subgroups based on competition age divisions (U14, U16, U18). Isometric hip ABD and AD strength in each leg was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…One of our most wondering findings was the noticeable higher predictive values of YBT-LQ performance in stance rather than kicking leg. A similar situation was noted in studies by other authors 25,31 , who suggested that regression models were significant for only one leg. In the remaining trials, only measurements and analysis were considered for one limb instead of both probably due to the belief that balance does not differ significantly between the dominant and non-dominant limbs 48 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…One of our most wondering findings was the noticeable higher predictive values of YBT-LQ performance in stance rather than kicking leg. A similar situation was noted in studies by other authors 25,31 , who suggested that regression models were significant for only one leg. In the remaining trials, only measurements and analysis were considered for one limb instead of both probably due to the belief that balance does not differ significantly between the dominant and non-dominant limbs 48 .…”
Section: Discussionsupporting
confidence: 84%
“…In Nelson's 6 kinetic model, hip ABD moment explained 23.4% of PM reach distance whereas PL direction performance was not predicted by hip ABD moment. The findings achieved by Dominguez-Navarro et al 25 also indicated that hip abductor strength was a significant predictor of composite score in young elite female basketball players. However, these results were only significant for right limb and, moreover, they analysed prediction of composite score without splitting into directional reaches.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Most existing studies on muscle strength parameters and profiles by position in soccer players have been developed at the knee level, evaluating the concentric and eccentric action of quadriceps and hamstrings [9][10][11]. However, it is also necessary to know these values at the hip level due to the great influence they have on sports performance [12][13][14][15] and lower extremity injuries [16]. There is scarce evidence regarding hip muscle strength values in soccer players by position.…”
Section: Introductionmentioning
confidence: 99%